2020
DOI: 10.1002/jemt.23576
|View full text |Cite
|
Sign up to set email alerts
|

Digital light microscopy to characterize the scales of two goatfishes (Perciformes; Mullidae)

Abstract: The normal and lateral line scales from above the head and four flank regions were investigated in two goatfishes by using light microscopy to evaluate the microscopic characteristics of scale surface ornamentation from different body parts of these fishes and to add new morphological data for their discrimination. The body scales were removed and digital images captured with a Dino‐Lite digital camera connected to a Leica compound microscope. The presence of both transverse and longitudinal radii was a distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(54 citation statements)
references
References 34 publications
3
51
0
Order By: Relevance
“…However, the comparison of scale variation from two examined body regions revealed that the scales from the caudal peduncle region demonstrated more sizedependent changes than those scales from below the dorsal fin. This confirms the previous studies that scale from different body regions may exhibit different surface ornamentations (e.g., Bräger & Moritz, 2016;Sabbah et al, 2020). The result of our study is also in agreement with the findings of Teimori et al (2021) in which the scales of small tooth-carps had often a large focus, while the scales of large fishes displayed often a small focus.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…However, the comparison of scale variation from two examined body regions revealed that the scales from the caudal peduncle region demonstrated more sizedependent changes than those scales from below the dorsal fin. This confirms the previous studies that scale from different body regions may exhibit different surface ornamentations (e.g., Bräger & Moritz, 2016;Sabbah et al, 2020). The result of our study is also in agreement with the findings of Teimori et al (2021) in which the scales of small tooth-carps had often a large focus, while the scales of large fishes displayed often a small focus.…”
Section: Discussionsupporting
confidence: 94%
“…They are placed in three categories, that is, cycloid, ctenoid, and spinoid (Roberts, 1993; Wainwright & Lauder, 2016). The previous studies have shown that differences in scale type and morphology often exist among clades (Arratia, 2000; Roberts, 1993), within clades (Ibanez & Jawad, 2018), and even within regions of a single individual (Dapar, Torres, Fabricante, & Demayo, 2012; Motamedi, Teimori, Masoumi, Mohammadzadeh Shaghooei, & Mousavi, 2019; Sabbah, Teimori, & Hesni, 2020). One of the first classifications of fishes was based on scales (see Agassiz, 1834; Arratia, 2000, see figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, scales were subjected to digital imaging using a Nikon Eclipse 80i Digital Imaging Head connected to a computer. The digital images were then used for morphological descriptions and measurements (Sabbah et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…However, the scale structure has lees been addressed in goatfishes of the Mullidae and are limited to Dapar et al (2012) on the Indian goatfish, Parupeneus indicus (Lacepède, 1802), and Sabbah, Teimori, and Askari Hesni (2020) on the Cinnabar goatfish, P. heptacanthus and Sulphur goatfish, Upeneus sulphureus (Cuvier, 1829).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation